Simultaneous determination of cadmium and lead in wine by electrothermal atomic absorption spectrometry - Freschi, GPG; Dakuzaku, C. S.; de Moraes, M.; Nobrega, J. A.; Neto, JAG (Elsevier B.V., 2001)
A method has been developed for the direct simultaneous determination of Cd and Pb in white and red wine by electrothermal atomic absorption spectrometry (ET-AAS) using a transversely heated graphite tube atomizer (THGA) with longitudinal Zeeman-effect background correction. The thermal behavior of both analytes during pyrolysis and atomization stages were investigated in 0.028 mol l(-1) HNO3 and in 1 + 1 v/v diluted wine using mixtures of Pd(NO3)(2) + Mg(NO3)(2) and NH4H2PO4 + Mg(NO3)(2) as chemical modifiers. With 5 mug Pd + 3 mug Mg as the modifiers and a two-step pyrolysis (10 s at 400 degreesC and 10 s at 600 degreesC), the formation of carbonaceous residues inside the atomizer was avoided. For 20 mul of sample (wine + 0.056 mol l(-1) HNO3, 1 + 1, v/v) dispensed into the graphite tube, analytical curves in the 0.10-1.0 mug l(-1) Cd and 5.0-50 mug l(-1) Pb ranges were established. The characteristic mass was approximately 0.6 pg for Cd and 33 pg for Pb, and the lifetime of the tube was approximately 400 firings. The limits of detection (LOD) based on integrated absorbance (0.03 mug l(-1) for Cd, 0.8 mug l(-1) for Pb) exceeded the requirements of Brazilian Food Regulations (decree #55871 from Health Department), which establish the maximum permissible level for Cd at 200 mug l(-1) and for Pb at 500 mug l(-1). The relative standard deviations (n = 12) were typically < 8% for Cd and < 6% for Pb. The recoveries of Cd and Pb added to wine samples varied from 88 to 107% and 93 to 103%, respectively. The accuracy of the direct determination of Cd and Ph was checked for 10 table wines by comparing the results with those obtained for digested wine using single-element ET-AAS, which were in agreement at the 95% confidence level. (C) 2001 Elsevier B.V. B.V. All rights reserved.
Keywords: simultaneous graphite furnace atomic absorption spectrometry; wine; direct analysis; cadmium; lead